Implementasi Metode Bercerita dalam Pembelajaran Menyimak untuk Meningkatkan Karakter Tanggung Jawab Siswa Sekolah Dasar - Adira Adzkia; Ibnu Muthi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to examine the implementation of the storytelling method as an effective strategy in character education in elementary schools. In the challenging era of globalization, students are not only required to be academically intelligent, but also to have strong characters and noble morals. The rapid flow of information and changes in social values ​​that occur require a learning approach that is able to build the moral foundation of students from an early age. The storytelling method is present as one solution because it is able to convey character values ​​in a fun, contextual, and touching way for children's emotions. This study uses a qualitative literature study approach, by reviewing various research results, scientific journals, articles, and books related to the application of the storytelling method in character learning. The results of the study show that stories can instill the values ​​of honesty, responsibility, empathy, tolerance, and cooperation more meaningfully. The active involvement of teachers as storytellers and learning facilitators has a major influence on building students' emotional involvement and creating a positive learning atmosphere. However, there are still challenges such as limited media, lack of teacher training, and limited time in class. Therefore, innovative strategies such as the use of audiovisual media, role-playing, and making stories with students are effective alternatives. In conclusion, the storytelling method is a potential approach to instilling character values ​​comprehensively and sustainably.